Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter?. Issue 6 (2nd July 2016) - Watts, Andrew J. R.; Albalat, Amaya; Smith, Ian P.; Atkinson, Robert J. A.; Neil, Douglas M.
ABSTRACT: Norway lobsters, Nephrops norvegicus, are sediment-dwelling decapod crustaceans that excavate burrows from which they make short excursions to feed by predation and scavenging. The females of this species are known to reside within their burrows for an extended period of time over the winter while brooding their eggs . The aim of this study was to assess the likelihood of these females being able to feed during this brooding period. Biophysical and biochemical measurements that had previously been shown to change with starvation under laboratory conditions in male N. norvegicus were taken for female N. norvegicus under similar conditions. These measurements were also compared in both sexes obtained from monthly trawl samples from the Clyde Sea Area, Scotland, UK, together with trawl composition data. The laboratory study showed that the hepatosomatic index, and the copper, lipid and water content of the hepatopancreas can be used as indicators of the state of starvation in females, as in males. In the wild, both sexes have reduced nutritional status during the winter, but not to the degree seen in animals starved for 20 weeks in aquarium trials. This study does not support the hypothesis that females cease feeding over winter, during their brooding period. Firstly, some females were unable to sustain ovary development during starvation under controlled conditions, contrary to field observations. Secondly, field data suggest that there is no sex-specific reduction in nutritional status.